Structural Change and Performance: Quantum Versus Piecemeal-Incremental Approaches - Miller, Danny; Friesen, Peter H. (Academy of Management Journal, 1982)
The effectiveness of different approaches to changing organization structure is examined. Two dimensions of structural change are explored. The findings show a tendency for quantum change, that is, change that is both concerted and dramatic, to be more associated with high performance than are piecemeal and incremental changes.